Developing Trust through Social Media Influencers and Halal Tourism to Impact the Travel Decision of Travelers - Abdullah, Muhammad; Khurshid, Muzammil; Khan, Muhammad Haris (Journal of Islamic and Religious Studies, 2022)
Marketers are trying their best to find tactics and means of communication to gain the trust of consumers by attracting them and keeping their needs and interests in view, like halal tourism in the domain of the hospitability industry. The main purpose of this study is to analyze and explain whether the trust is developed by Social Media influencers and Halal Tourism and hence impacts the travel decision of travelers or not, in the context of Pakistan. In this regard, the data is collected from university students of the University of Punjab Gujranwala Campus and GIFT University. After collection different tests of normality, correlation, regression, and mediations were run on the data for analysis by using statistical software SPSS 20. After analysis, it was found that all hypotheses are accepted and interpreted that Social Media Influencers and Halal Tourism significantly impact the decisions of travelers. The study also revealed that trust mediates the relationship between Social Media influencers and Travel decisions; as well as the relation between Halal Tourism and Travel decisions. Organizations and managers must use these findings and knowledge to attract consumers and enhance their profits. These findings contribute to theory as it is the first study of its type and paves way for future research.